Engineering metal–organic frameworks for adsorption-based gas separations: from process to atomic scale. Issue 11 (16th September 2021) - Taddei, Marco; Petit, Camille
Abstract : An overview of the state-of-the-art and of the main challenges in the field of adsorption-based gas separations using metal–organic frameworks. Abstract : Metal–organic frameworks (MOFs) are the object of intense research targeting their deployment as adsorbents for a wide range of gas separations, such as CO2 capture, biogas upgrading, air separation and small hydrocarbon separation. The scope of this review is to provide chemists, materials scientists and engineers with an overview of the state-of-the-art and of the main challenges in the field of adsorption-based gas separations using MOFs. To do so, we first discuss current gas separation challenges for which adsorption could play a role. The following three sections of the paper describe process-level considerations in the design, selection and deployment of MOFs as sorbents and subsequently focus on material-level considerations. Both the process and the material aspects cover experimental and computational work. Going from the process scale to the atomic scale, we aim to highlight the links and synergies between the two and identify the current barriers that hamper the development of adsorption-based gas separations using MOFs as sorbents. Throughout the article, we also provide fundamental and technical information related to MOF design, synthesis, characterisation and sorption testing.